STRATEGI KOMUNIKASI DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN KUANTAN SINGINGI DALAM MEMPROMOSIKAN BUDAYA PERAHU BAGANDUANG - Ilham Fajri; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Based on the data that researchers get from the Department of Culture and Tourism Kuantan Singingi regency that there is indeed less interest people to cultural traditions boat baganduang. The purpose of this research is to know the strategy of audience, strategy of message, and strategy of choosing / using media used by Culture and Tourism Office of Kuantan Singingi Regency in promoting boat culture to society.In this study the authors use descriptive qualitative research methods with data collection techniques are grouped through observation, interview and documentation. Informants in this study amounted to 9 people taken based on the technique of purposive sampling, the Head of Culture and Tourism Office of Kuantan Singingi, Public Relation and Tourism Office of Kuantan Singingi Regency, Head of Marketing and Economy Division of Culture and Tourism Office of Kuantan Singingi Regency, 3 visitors which witnessed the culture of baganduang boat and 3 visitors who have never witnessed the culture of baganduang boat. Interactive data analysis model of the researcher used to describe the result of research in data analysis technique and to check the validity of data of researcher using triangulation technique.The results showed that the communication strategy of the Department of Culture and Tourism of Kuantan Singingi Regency in promoting the culture of baganduang boat that is from the determination of the audience is the whole community of Lubuk Jambi, Kuantan Mudik Subdistrict and surrounding areas in Kuantan Singingi Regency. After that the strategy message used is the content of messages that are persuasive and informative, which is packed with how to create a short message that attracts the attention of audiences and messages using the symbol / pictures. And the last media strategy used by the Office of Culture and Tourism Kuantan Singingi Regency in promoting the culture of baganduang boat is electronic media, online media, and print media campaign.Keyword: Communication Strategy, Promoting